STUDENTS’ PERCEPTIONS OF SONGS IN DEVELOPING THEIR VOCABULARY ACHIEVEMENT - Anaura Izdihar, Khansa; Novita Sari, Heni (ELLTER Journal, 2025)
The aim of this study was to explore how students perceive the use of songs in developing their vocabulary achievement. Vocabulary was considered important for language acquisition, and songs were believed to provide contextualization, repetition, and fun learning. This quantitative study was conducted at Education Training Course in Depok, Indonesia, with 25 students who were already familiar with learning through songs. A Likert-scale questionnaire was used to obtain students’ perceptions, while a vocabulary test was used to assess their vocabulary achievement. The results showed positive perceptions, with a mean agreement of 84.32 out of 100. The results of the vocabulary test were also high, with 81% of questions answered correctly. A significant positive correlation was found between students’ positive perceptions and their vocabulary performance (ρ = 0.859, p < 0.01). These findings indicated that students held positive perceptions toward the use of the songs and that songs played a supportive role in developing their vocabulary achievement.